Applying Acoustic Emission Technique for Detecting Various Damages Occurred in PCL Nanomodified Composite Laminates - Ali Gholizadeh (MDPI AG, 2021)
Interleaving composite laminates by nanofibers is a well-known method of increasing interlaminar fracture toughness. Among many possibilities, polycaprolactone (PCL) nanofibers is one of the best choices for toughening composite laminates. The influence of PCL on delamination mode of failure is considered before. However, the effect of PCL on other damage modes, such as fiber breakage and matrix cracking, is yet to be studied. In this study, the acoustic emission (AE) technique is applied to determine the effect of toughening composite laminates by PCL nanofibers on matrix cracking, fiber/matrix debonding, and fiber breakage failure mechanisms. For this purpose, mode I and mode II fracture tests are conducted on modified and non-modified glass/epoxy laminates. Three different methods, i.e., peak frequency, wavelet transform, and sentry function, are utilized for analyzing the recorded AE data from mode I test. The results show that applying PCL nanofibers not only increases the mode I critical strain energy release rate by about 38%, but also decreases different failure mechanisms by between 75 and 94%.